Do established SNPs affecting bovine milk traits exist in other dairy ruminants? - Miltiadou, Despoina; Tzamaloukas, Ouranios; Genethliou, Nicholas; Chatziplis, Dimitrios G.; Orford, Michael R.; Papachristoforou, Christakis (My University, 2010)
To assess whether established single nucleotide polymorphisms (SNPs) affecting bovine milk traits are present in small ruminants, we genotyped samples from Chios and Cyprus fat-tailed sheep, as well as Damascus and Machaeras goats for the presence of the acylCoA:diacylglycerol acyltransferase 1 (DGAT1) K232A and the growth hormone receptor (GHR) F279Y SNPs. Both of these SNPs have been previously well documented in cattle as having strong effects on milk yield and composition and have been postulated as being the causative mutations to partially explain QTLs identified on bovine chromosomes 14 and 20. Although we were able to confirm the presence of both of these mutations in bovine sample controls by both allele specific PCR reactions and direct DNA sequencing, we were unable to detect them in any of the four major pure breeds of sheep and goats supporting the dairy industry of Cyprus.
Keywords: Sheep; Goats; Milk production traits; Growth hormone receptor; DGAT1; SNPs